POTENSI LAHAN DI DESA KAHUKU KECAMATAN LIKUPANG KABUPATEN MINAHASA UTARA BERDASARKAN KELAS KEMAMPUAN - Maya Pinamangung; Joice M.J. Supit; Jeanne Lengkong; Tommy D. Sondakh (Universitas Sam Ratulangi, 2013)
ABSTRACTLand use without regard to its ability to cause a decrease in the quality of the land, land degradation because they will affect the potential of land. Determine land capability class is expected that the potential of land owned by the obvious. This study aims to assess the potential of rural land capability classes based Kahuku. Research results showed that land potentially useful views of the class abilities gained in the research area of land where two six-unit class III land units with an area of 8.5 ha and a four unit class IV land with total area of 67.35 hectares.Key words : Potential Land, Capability Land